Faire pays dans un cyberespace : le cas des Haïtiens en Île-de-France - Rébecca Cadeau (EchoGéo)
This article seeks to understand the socio-spatial impacts of Information and Communication Technologies (ICT) utilization in a diasporic context. The study of the uses of dedicated applications and socio-digital networks by diaspora associations, allows us to analyze the ways in which Haitians make themselves present « here », « there » and « elsewhere », in order to continue « making their country » in the « territories of dispersal ». We explore the mechanisms of structuring the group around an "origin referent" through which migrants become a « social formation » outside their society, while remaining attached and connected to it remotely.